Social Security of Disabled People in Poland Against the Background of European Union Countries - Organiściak-Krzykowska, Anna; Wiśniewski, Tomasz (Acta Universitatis Lodziensis. Folia Oeconomica, 2020)
The aim of this article is to classify the security systems for disabled people within the European Union in relation to the Polish social security system in light of other European Union countries. The results were based on economic indicators such as: the role of expenses for disabled people within the overall national social expenses and GDP as well as the expenses for people with disability per capita. The analysis of the chosen countries took place mostly based on documents published by the European commission. The time period included the years 2009–2016. Based on the classification which has been carried out it has been concluded that the Polish social security system can be considered mid‑advanced. The countries which were considered to have a highly developed social security system for people with disability included mostly Scandinavian countries (Switzerland, Finland, Denmark). Countries with the lowest advancement rate for their social security system for people with disability included, among others, Cyprus and Malta.